2015
DOI: 10.1007/s10895-015-1644-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interaction, Photocleavage and Topoisomerase I Inhibition by Ru(II) Complex with a New Ligand Possessing Phenazine Unit

Abstract: A new ruthenium complex with a dppz-like ligand pyidppz, [Ru(bpy)2(pyidppz)](2+) (pyidppz = 2-(pyridine-2-yl)imidazo-[4,5-b]dipyrido-[3,2-a:2',3'-c]phenazine) has been synthesized and characterized by ES-MS, elemental analysis, (1)H NMR. Intercalative mode of the complex bound to calf thymus DNA has been supported by different spectroscopic methods and viscosity measurements. The introduction of phenazine unit may be one of the main reasons for the weak emission of Ru(II) complex in aqueous solution. Under irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In the ESI‐MS spectra in CH 3 CN, two main peak signals for complex 1 and 2 , [M − 2PF 6 − − H] + and [M − 2PF 6 − ] 2+ , were observed, the latter appearing as the major peak. Ru (II) complexes 1 and 2 displayed resolvable 1 H NMR spectra in DMSO‐ d 6 , and all proton chemical shifts were assigned based on a comparison with those of similar compounds (Figure S1). In the 1 H NMR spectra of the complexes, a clean singlet peak appears at 13.80 and 13.76 ppm corresponding to the imidazole proton for 1 and 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ESI‐MS spectra in CH 3 CN, two main peak signals for complex 1 and 2 , [M − 2PF 6 − − H] + and [M − 2PF 6 − ] 2+ , were observed, the latter appearing as the major peak. Ru (II) complexes 1 and 2 displayed resolvable 1 H NMR spectra in DMSO‐ d 6 , and all proton chemical shifts were assigned based on a comparison with those of similar compounds (Figure S1). In the 1 H NMR spectra of the complexes, a clean singlet peak appears at 13.80 and 13.76 ppm corresponding to the imidazole proton for 1 and 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although CPT and its derivatives displayed good topo I inhibition and antitumor activities, their cell resistance and low water solubility reduce antitumor activity and topo I inhibition . Recently, ruthenium‐based compounds have also been found to show excellent antitumor activity and significant inhibitory activity against DNA topo I, with many studies indicating that they show excellent DNA‐binding ability, good solubility properties in water, low toxicity and high stability under physiological conditions . For example, our group reported that [Ru (bpy) 2 (pyip)] 2+ (pyip = 2‐(pyridine‐2‐yl)imidazo‐[4,5‐ f ]1,10‐phenanthroline) exhibited good inhibition activity against DNA topo I (IC 50 ~ 16 μM) …”
Section: Introductionmentioning
confidence: 99%
“…have reported the DNA intercalative agents based on ruthenium complexes containing intercalative ligand dppz and pip (dppz = dipyrido[3,2‐ a :2’,3’‐ c ]phenazine, pip = 2‐phenylimidazo[4,5‐ f ][1,10]phenanthroline) showed remarkable topo inhibition activity. Our group has also reported that [Ru(bpy) 2 (pyip)] 2+ (bpy = 2, 2’‐bipyridine, pyip = 2‐(pyridine‐2‐yl)imidazo‐[4,5‐ f ][1,10]‐phenanthroline) showed good inhibition activity against DNA topo I (IC 50 ~ 16 μM) …”
Section: Introductionmentioning
confidence: 97%
“…It is an important nuclear enzyme in cellular process that can control the topological state of DNA . Many studies have shown that a variety of antitumor drugs have been found to inhibit DNA topoisomerase . For example, camptothecin and its derivatives are known to be the inhibitors of DNA Topo I and show excellent antitumor activity against a broad spectrum of tumor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation